2017
DOI: 10.4103/0366-6999.218012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Helicobacter pylori Infection and Diabetic Gastroparesis

Abstract: Background:Whether Helicobacter pylori infection is associated with diabetic gastroparesis (DGP) is unclear. This study aimed to investigate the potential correlation between H. pylori infection and DGP.Methods:In this study, 163 patients with type 2 diabetes mellitus and 175 nondiabetic patients who were treated in our department were divided into DGP, simple diabetes, non-DGP (NDG), and normal groups based on their conditions. The H. pylori infection rate in each group was calculated. H. pylori eradication t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The results of the present study showed that the gastric emptying rate of the mice infected with HP was significantly lower than that of noninfected mice, which is consistent with the results of previous studies ( 5 , 6 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study showed that the gastric emptying rate of the mice infected with HP was significantly lower than that of noninfected mice, which is consistent with the results of previous studies ( 5 , 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…Patients with DGE suffer from nutritional deficiencies and metabolic consequences as well as impairment of social activities and quality of life ( 18 , 35 ). There have been a number of studies on the relationship between HP infection and DGE, and it has been reported that HP infection can retard the gastric emptying function and induce DGE, but the specific mechanism has rarely been studied ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have analyzed the prevalence of H. pylori infection in symptomatic and asymptomatic patients with DM [ 32 , 33 , 34 ]. Hyperglycemia has been suggested as a predisposing factor for H. pylori colonization [ 32 ].…”
Section: H Pylori Infection In Patients With Dmentioning
confidence: 99%
“…Among patients with DM, H. pylori infection has been shown to be higher in patients with gastroparesis, and bacterial eradication reduced symptoms such as upper abdominal pain and distention, early satiety and anorexia [ 34 ], thus suggesting a pathogenetic role of H. pylori in DG and reaffirming the therapeutic role of its eradication.…”
Section: H Pylori Infection In Patients With Dmentioning
confidence: 99%
“…Within a large diabetic population, the prognosis of patients with proteinuria is serious, and there is a certain coping strategy for HP infection. [ 20 21 ] An increasing amount of research focuses on the interaction between HP infection and renal function. However, controversy still exists about the association between HP infection and the occurrence of proteinuria in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%